2019
DOI: 10.1002/jor.24417
|View full text |Cite
|
Sign up to set email alerts
|

Acute Changes in NADPH Oxidase 4 in Early Post‐Traumatic Osteoarthritis

Abstract: Knee injuries cause structural damage and acute inflammation that initiates the development of post‐traumatic osteoarthritis (PTOA). NADPH oxidase 4 (Nox4), a member of a family of enzymes that generates reactive oxygen species (ROS), plays a pivotal role in normal development of the musculoskeletal system, but may increase ROS production to harmful levels after joint injury. The role of ROS in both normal joint homeostasis and injury is poorly understood, but inhibition of excessive ROS production by Nox4 aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 34 publications
1
33
0
Order By: Relevance
“…There is a study that investigated the clinical utility of selective iNOS inhibitors as disease-modifying OA drugs, as they have been shown to reduce joint inflammation and erosion in animal models of OA. The same study demonstrated that nNOS is more frequently expressed by normal chondrocytes, while iNOS prevails in OA chondrocytes [49].…”
Section: Ros Production In Chondrocytesmentioning
confidence: 66%
“…There is a study that investigated the clinical utility of selective iNOS inhibitors as disease-modifying OA drugs, as they have been shown to reduce joint inflammation and erosion in animal models of OA. The same study demonstrated that nNOS is more frequently expressed by normal chondrocytes, while iNOS prevails in OA chondrocytes [49].…”
Section: Ros Production In Chondrocytesmentioning
confidence: 66%
“…99 In a mouse model of post-traumatic osteoarthritis induced by ACL-rupture, Nox4 activity was acutely decreased within 24 hours of injury, and this was followed by a subsequent increase of Nox4 activity. 75 Inhibition of Nox4 using GKT137831 was protective against early structural changes in the mouse knee joints, suggesting a possible role for Nox4 in the pathogenesis of post-traumatic osteoarthritis. 75…”
Section: Arthritismentioning
confidence: 96%
“…75 Inhibition of Nox4 using GKT137831 was protective against early structural changes in the mouse knee joints, suggesting a possible role for Nox4 in the pathogenesis of post-traumatic osteoarthritis. 75…”
Section: Arthritismentioning
confidence: 96%
“…NOX4 constitutively produces hydrogen peroxide (H 2 O 2 ) [45] and participates in the development and homeostasis of tissues that make up normal joints [46]. NOX4 plays a signi cant role in the acute phase after joint injury, and targeted inhibition of in ammation caused by NOX4 may help prevent early joint changes in the pathogenesis of post-traumatic osteoarthritis [47]. However, the role of NOX4 in the OA progress and resveratrol treatment remains blank.…”
Section: Discussionmentioning
confidence: 99%